The reliability, validity and responsiveness of the Thai version of systemic lupus erythematosus quality of life (SLEQOL-TH) instrument - N. Kasitanon (2018)
Objectives: The English version of the Systemic Lupus Erythematosus Quality of Life Questionnaire (SLEQOL) is a validated disease-specific quality of life instrument. The aim of this study was to evaluate the psychometric properties of the Thai version of the SLEQOL (SLEQOL-TH). Methods: Two independent translators translated the SLEQOL into Thai. The back translation of this version was performed by two other independent translators. The final version, SLEQOL-TH, was completed after resolving the discrepancies revealed by the back translation. One hundred and nine patients with SLE were enrolled to test the reliability, construct validity, floor and ceiling effects, and sensitivity to the changes of the SLEQOL-TH at six months. The differential item functioning (DIF) between the Thai and English versions was analyzed using the partial gamma. Results: The internal consistency of the SLEQOL-TH was satisfactory with the overall Cronbachs alpha of 0.86. The test-retest reliability of the SLEQOL-TH was acceptable with the intra-class correlation coefficient of 0.86. Low correlations between the SLEQOL-TH and SLEDAI were observed. The total score of the SLEQOLTH was moderately responsive to changes in quality of life, with a standardized response mean of 0.50. When comparing the SLEQOL-TH from Thai SLE patients with the original SLEQOL version obtained from Singapore SLE patients, 11 out of 40 items showed a moderate to large DIF. Conclusions: The SLEQOL-TH has acceptable psychometric properties and shows construct validity. In comparison with the English version of SLEQOL, there are some items that showed DIF. The applicability of the SLEQOL-TH in real-life clinical practice and clinical trials needs to be determined. Lupus (2013) 22, 289296.© The Author(s), 2012.